AWARENESS LEVEL OF BENEFICIARIES TOWARDS PRADHAN MANTRI JAN DHAN YOJANA (PMJDY) – A STUDY - 1. Suman Rani , 2. Dr. Mahipal Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The Pradhan Mantri Jan-DhanYojana (PMJDY) is a National Mission for Financial Inclusion that aims to provide an affordable access to financial services to the disadvantaged group of the society with the help of zero balance savings accounts. It is a crucial government initiative aimed at achieving widespread financial inclusion and progressing towards inclusive growth. This paper aims to study this scheme in details as well as its progress since beginning and to analyze the awareness level of beneficiaries towards this scheme. The study used a descriptive and exploratory research design in which survey method was used to collect the data from 40 respondents of Delhi –NCR with the help of multistage sampling. To meet the objectives both primary and secondary data has been used. Primary data has been collected with the help of structured questionnaire and secondary data has been collected from official websites of ministry of finance and various reputed journals and collected data has been analyzed with the help of descriptive statistics like frequency, percentage, mean and standard deviation. The study concluded that PMJDY has not only brought millions of previously unbanked households into the financial fold but also create a remarkable record of 53.13 crore bank accounts opening. The study suggested that some awareness programme should be organize to educate the people regarding the features of this scheme, so that the people may be benefitted.